Effect of zakat (almsgiving) literacy level on muzakki’s decision to pay zakat in registered zakat institutions - Atiqa Syaksena; Marlina Ekawaty (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
Purpose – This study aims to determine the effect of the zakat (almsgiving) literacy level and several other factors on the decision of muzakki to pay zakat at the registered zakat institutions in Situbondo Regency.Method – This study uses a quantitative approach with logistic regression analysis. Result – The zakat literacy level, education, and trust have a positive and significant effect on the decision of muzakki to pay zakat at registered zakat institutions. The income variable in this study has no significant effect on the decision of muzakki to pay zakat at the registered zakat institutions in Situbondo Regency.Implication – This study gives insight about the role of zakat literacy in increasing zakat payment. This study could assist government to increase zakat payment.Originality – The use of the Simple Weighted Index (SAWI) method to find the value of the Zakat Literacy Index.